2010
DOI: 10.1021/ic902427r
|View full text |Cite
|
Sign up to set email alerts
|

Photobiological Activity of Ru(II) Dyads Based on (Pyren-1-yl)ethynyl Derivatives of 1,10-Phenanthroline

Abstract: Several mononuclear Ru(II) dyads possessing 1,10-phenanthroline-appended pyrenylethynylene ligands were synthesized, characterized, and evaluated for their potential in photobiological applications such as photodynamic therapy (PDT). These complexes interact with DNA via intercalation and photocleave DNA in vitro at submicromolar concentrations when irradiated with visible light (λ irr g 400 nm). Such properties are remarkably sensitive to the position of the ethynylpyrenyl substituent on the 1,10-phenanthroli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 84 publications
2
88
0
Order By: Relevance
“…designed and tested the PDT efficiency of Ru(II) polypyridyl complexes that had the lowest-lying 3 IL-based excited states, with remarkably long lifetimes (from 22 to 270 μs), by linking pyrenylethynylene derivatives ligands, 257259 which made the complexes hold higher 1 O 2 quantum yields compared to [Ru(bpy) 3 ] 2+ . These complexes interacted with DNA via intercalation and produced photocleavage of DNA in vitro at submicromolar concentrations when irradiated with visible light.…”
Section: Ruthenium(ii) Polypyridyl Complexesmentioning
confidence: 99%
“…designed and tested the PDT efficiency of Ru(II) polypyridyl complexes that had the lowest-lying 3 IL-based excited states, with remarkably long lifetimes (from 22 to 270 μs), by linking pyrenylethynylene derivatives ligands, 257259 which made the complexes hold higher 1 O 2 quantum yields compared to [Ru(bpy) 3 ] 2+ . These complexes interacted with DNA via intercalation and produced photocleavage of DNA in vitro at submicromolar concentrations when irradiated with visible light.…”
Section: Ruthenium(ii) Polypyridyl Complexesmentioning
confidence: 99%
“…The photocytotoxicity of the complexes toward human leukemia cell lines (HL-60) and metastatic melanoma cell line Malme-3M was also investigated as a function of the placement of the pyrenylethynylene substituent on the phen ligand [76,77]. The [Ru(bpy) 2 (3-pyr-phen)] 2+ , [Ru(bpy) 2 (4-pyrphen)] 2+ , and [Ru(bpy) 2 (5-pyr-phen)] 2+ complexes (Fig.…”
Section: Oxygen-independent Dna Modificationmentioning
confidence: 99%
“…It has been demonstrated that inorganic complexes can be used in footprinting studies, as sequence specific DNA binding agents, as diagnostic agents in medicinal applications, and for genomic research. Among different modes of DNA cleavage, oxidative cleavage of DNA upon irradiation with visible light is of main interest due to the potential applications of such compounds in photodynamic therapy of cancer [3, 15] and references therein.…”
Section: Introductionmentioning
confidence: 99%